The Effect of Internal Controls on the Profitability of Nepalese Commercial Banks - Bhatta, Uddhav Dev (Nepalese Journal of Finance, 2025)
The study examines the effect of internal controls on the profitability of Nepalese commercial banks. Profitability is dependent variables. The selected independent variables are control environment, risk assessment, control activities, information and technology and monitoring. The primary source of data is used to assess the opinions of respondents regarding control environment, risk assessment, control activities, information and technology, monitoring and profitability of Nepalese commercial banks. The study is based on primary data of 127 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of internal controls on the profitability of Nepalese commercial banks. The study demonstrated a positive impact of control environment on the profitability of Nepalese commercial bank. It indicates that when commercial bank increase the focus on control environment, they earn maximum profit. Similarly, the study revealed a positive impact of risk assessment on the profitability of Nepalese commercial bank. It indicates that better risk assessment in internal controls boost the profitability of Nepalese commercial bank. Likewise, the study showed a positive impact of control activities on the profitability of Nepalese commercial bank. It indicates that the control activities are useful to lead the profitability of Nepalese commercial bank. Further, the study observed a positive impact of information and technology on the profitability of Nepalese commercial bank. Use of advanced information and technology is useful to lead the profitability of commercial bank. It indicates that the optimum utilization of information and technology are useful to lead the profitability of Nepalese commercial bank. In addition, the study found a positive effect of monitoring on the profitability of Nepalese commercial bank. It indicates that higher level of the monitoring in internal control activities helps to enhance the profitability of Nepalese commercial bank. Overall, these findings underscore the significant role of control environment, risk assessment, control activities, information and technology and monitoring to increase the profitability of Nepalese commercial bank.